A note on controllability of semilinear integrodifferential systems in Banach spaces. (2000) - Balachandran, K.; Sakthivel, R.
Abstract : Sufficient conditions for controllability of semilinear integrodifferential systems in a Banach space are established. The results are obtained by using the Schaefer fixed-point theorem.